Study of B+c decays to charmonia and three light hadrons - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2022)
Using proton-proton collision data, corresponding to an integrated luminosity of 9 fb−1 collected with the LHCb detector, seven decay modes of the B+c meson into a J/ψ or ψ(2S) meson and three charged hadrons, kaons or pions, are studied. The decays B+c → (ψ(2S) → J/ψπ+π−)π+, B+c → ψ(2S)π+π−π+, B+c → J/ψK+π−π+ and B+c → J/ψK+K−K+ are observed for the first time, and evidence for the B+c → ψ(2S)K+K−π+, decay is found, where J/ψ and ψ(2S) mesons are reconstructed in their dimuon decay modes. The ratios of branching fractions between the different B+c decays are reported as well as the fractions of the decays proceeding via intermediate resonances. The results largely support the factorisation approach used for a theoretical description of the studied decays.
*The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, N. Meinert, D.J. Unverzagt, U. Uwer, H. Viemann, C. Wang, L. Witola, A. Zhelezov [und sehr viele weitere Personen]
Im Titel ist das Pluszeichen hochgestellt
Im Titel ist der Buchstabe c tiefgestellt
Gesehen am 14.02.2022